Suberites microstomus var. stellatus Kirkpatrick 1908 ... - Van Soest, Rob W. M. (Zenodo, 2024)
Suberites microstomus var. stellatus Kirkpatrick, 1908 (Fig. 10A) Suberites microstomus var. stellatus Kirkpatrick, 1908: 19, pl. XV figs. 8–13; Burton 1932: 336; Hentschel 1914: 52. The variety was described by Kirkpatrick from Winter Quarters, Antarctic, approximate coordinates 77.8333°S 166°E, depth 238 m (syntypes BMNH 1908.2.5.113–114). The variety differs from the typical variety described by Ridley & Dendy (1887: 199, pl. XLI fig. 3, from the region between Kerguelen and Heard Island, Challenger Exped. Stat.150, 52.0667°S 71.3667°E, depth 274 m, holotype BMNH 1887.5.2.86) in the greater thickness of the spicules (>20 µm vs. up to 15 µm in the typical variety) and having ‘stellar’ oscules vs. rounded oscules in the type. These differences appear quite small (Hentschel complained he could not see the ‘stellate’ oscules, Burton only listed the variety from South Georgia). For the time being I propose to merge the varieties into a single species, to be named Suberites microstomus Ridley & ... : Published as part of Van Soest, Rob W. M., 2024, Correcting sponge names: nomenclatural update of lower taxa level Porifera, pp. 1-122 in Zootaxa 5398 (1) on page 89, DOI: 10.11646/zootaxa.5398.1.1, http://zenodo.org/record/10494167 ...